Pelatihan Pembuatan Silase Jerami Padi Sebagai Pakan Ternak di Desa Manera Kecamataman Salomekko Kabupaten Bone: Pengabdian - Muh.Syawal; Nadia Vega; Ramlah; Marwah Umar; Ayunita Rahma; Abdul Razak Samal; Syaiful; Muhammad Rusdi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Based on observations during the Community Service Program (KKN) in Manera Village, Salomekko District, Bone Regency, it was identified that the majority of residents work as farmers and livestock breeders. Rice straw, as agricultural waste, is often not optimally utilized, even though it has the potential to be used as silage as a nutritious animal feed. The aim of this program is to provide training to the community on practical, efficient rice straw silage making techniques that can increase the availability of animal feed throughout the year. Activities are carried out through extension methods, direct demonstrations, and practice with the Manera village community. The results of the activities show high community enthusiasm and increased skills in processing rice straw into quality animal feed.